Star-polymer–colloid mixtures - Dzubiella, J.; Jusufi, A. (Condensed Matter Physics, 2002)
Recent results in theory and simulation of star-polymer–colloid mixtures
are reviewed. We present the effective interaction between hard, colloidal
particles and star polymers in a good solvent derived by monomer-resolved
Molecular Dynamics simulations and theoretical arguments. The relevant
parameters are the size ratio q between the stars and the colloids, as well
as the number of polymeric arms f (functionality) attached to the common
center of the star. By covering a wide range of q ’s ranging from zero
(star against a flat wall) up to about 0.5, we establish analytical forms for
the star-colloid interaction which are in excellent agreement with simulation
results. By employing this cross interaction and the effective interactions
between stars and colloids themselves, a demixing transition in the
fluid phase is observed and systematically investigated for different arm
numbers and size ratios. The demixing binodals are compared with experimental
observations and found to be consistent. Furthermore, we map the
full two-component system on an effective one-component description for
the colloids, by inverting the two-component Ornstein-Zernike equations.
Some recent results for the depletion interaction and freezing transitions
are shown. Зроблено огляд недавніх робіт про теорію та чисельне моделювання
сумішей зіркових полімерів і колоїдних частинок. Приведено потенціал ефективної взаємодії між твердими колоїдними частинками і зірковими полімерами в доброму розчиннику, отриманий з комп’ютерного моделювання мономерів методами молекулярної динаміки та з
теоретичних аргументів. Суттєвими параметрами потенціалу є співвідношення розмірів зірок і колоїдів q , а також кількість полімерних
гілок (функціональність) f , приєднаних до спільного центра зірки.
Знайдено аналітичну форму потенціалу взаємодії зірка-колоїд у широкій ділянці зміни q від нуля (зірка навпроти плоскої стінки) до величини порядку 0.5. Знайдена функція чудово узгоджується з результатами комп’ютерного моделювання. Використовуючи цей потенціал взаємодії, а також потеціали взаємодії між самими зірками і колоїдами, спостережено перехід розшарування в плинній фазі і проведено його систематичне дослідження для різної кількості ланцюгів
і співвідношення розмірів. Бінодалі розшарування порівняно з експериментальними спостереженнями і виявлено взаємне узгодження. Більше того, ми зображуємо повну двокомпонентну систему як
ефективну однокомпонентну для колоїдів, перетворюючи двокомпонентні рівняння Орнштайна-Церніке. Показано деякі недавні результати для взаємодії збіднення (depletion interaction) і фазових переходів в заморожений стан.